Seasonal effect on growth performance and leaf biomass production of two Moringa oleifera Lam. varieties grown under Sahelian condition in Burkina Faso - Kagambèga, Francois W.; Bagagnan, Abdoul Rasmane; Sawadogo, Louis; Ayantunde, Augustine A. (Sciencedomain International, 2019)
Aims: An experiment was conducted to compare the growth performance of two varieties of Moringa oleifera (wild variety and PKM-1) under different seasonal period at two locations in northern Burkina Faso, and the potential for improving household nutrition. Study Design, Place and Duration of Study: Two separate trials corresponding to sowing period (cold and warm) were laid out at each site (Bani and Tougou) in a completely randomized block design with three replicates between December 2017 and September 2018. Methodology: Each block was subdivided into two plots of 8 m² (separated from each other by 3 m break) intended to receive each variety of Moringa at each sowing period. The seeds were sown with 2 seeds by pit at 2 cm depth with spacing of 0.5 m x 0.5 m in each plot ploughed up to 30 cm. Watering was done daily during the dry season and consisted of applying 24 liters of water in each plot at two times. Vegetative growth measurements (plant height, number of leaves) were done weekly while leaf biomass production was assessed monthly from the 40th day after sowing. Results: The results showed that seedlings growth parameters and foliar biomass differed significantly (p < 0.001) among the two Moringa oleifera varieties and were influenced by the sowing period and sites. Although the two varieties grew well, Moringa oleifera var PKM-1 grew faster and produced much leaves compared to the wild or local variety. Then, greater growth attributes (height and number of leaves) and foliar biomass were noted for PKM-1. Conclusion: The warm period (March / April) appear to be the most recommendable period for the growth and biomass accumulation of the two varieties of Moringa oleifera.